2011
DOI: 10.1186/1556-276x-6-402
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface properties on the electrical conductivity of silicon nanomembranes

Abstract: Because of the large surface-to-volume ratio, the conductivity of semiconductor nanostructures is very sensitive to surface chemical and structural conditions. Two surface modifications, vacuum hydrogenation (VH) and hydrofluoric acid (HF) cleaning, of silicon nanomembranes (SiNMs) that nominally have the same effect, the hydrogen termination of the surface, are compared. The sheet resistance of the SiNMs, measured by the van der Pauw method, shows that HF etching produces at least an order of magnitude larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
3
15
0
Order By: Relevance
“…6(a), 8(b) and 8(d)). The conductivity of semiconductor nanomembranes will be sensitive to surface and/or interface properties as the large surface to volume ratio in the nanomembrane reduces the sheet density of dopants, 37 and hence, the influence of dopants on the electrical properties of the nanomembrane. Enhanced electron mobilities have been associated with semiconductor thin films with excellent quality interfaces and surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…6(a), 8(b) and 8(d)). The conductivity of semiconductor nanomembranes will be sensitive to surface and/or interface properties as the large surface to volume ratio in the nanomembrane reduces the sheet density of dopants, 37 and hence, the influence of dopants on the electrical properties of the nanomembrane. Enhanced electron mobilities have been associated with semiconductor thin films with excellent quality interfaces and surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed extensive investigations of the surface of bulk Si after treatment in HF have been conducted in the past decades, revealing that the Si surface is primarily terminated by hydrogen, with some fluorine also detected . As‐released NMs have an identical surface termination as bulk Si treated in HF . Once the NM/PDMS is immersed in solvent, the PMDS starts swelling.…”
Section: Resultsmentioning
confidence: 99%
“…More experimental works have recently been done by the same group 63–65. It was found that a 2 × 1 reconstruction is experimentally difficult to obtain.…”
Section: Ultra‐thin Nanomembranesmentioning
confidence: 99%